A novel role of FKN/CX3CR1 in promoting osteogenic transformation of VSMCs and atherosclerotic calcification. (November 2020) - Yang, Tong; Guo, Lu; Chen, Lizhao; Li, Jingcheng; Li, Qiong; Pi, Yan; Zhu, Jie; Zhang, Lili
Graphical abstract: Highlights: First targeting on the FKN/CX3CR1, osteogenic transformation of VSMCs and atherosclerotic calcification. Research on both vitro and vivo (ApoE −/− and ApoE -/- /CX3CR1 −/− mice involved). Lentivirus transfected CX3CR1 knockdown or overexpression to study the role of FKN in VSMC osteogenic transformation. Confirmed that FKN/CX3CR1 up-regulate RUNX2, suppress OPG through Jak2/Stat3 signaling pathway. Provide new strategies for the prevention and treatment of atherosclerotic calcification. Abstract: Fractalkine (FKN) and its specific receptor CX3CR1 play a critical role in the pathogenesis of atherosclerosis including recruitment of vascular cells and the development of inflammation. However, its contribution to regulating the development of atherosclerotic calcification has not been well documented. Osteogenic transformation of vascular smooth muscle cells (VSMCs) is critical in the development of calcification in atherosclerotic lesions. In this study, for the first time, we evaluated the effect of FKN/CX3CR1 on the progression of VSMCs calcification and defined molecular signaling that is operative in the FKN/CX3CR1-induced osteogenic transformation of VSMCs. We found that high-fat diet induced atherosclerotic calcification in vivo was markedly inhibited in the Apolipoprotein E (ApoE) and CX3CR1 deficient (ApoE −/− /CX3CR1 −/− ) mice compared with their control littermates. FKN and CX3CR1 were both expressed in VSMCs and up-regulated by oxidized low-density lipoprotein (ox-LDL). FKN/CX3CR1 promoted the expression of osteogenic markers, including osteopontin (OPN), bone morphogenetic protein (BMP)-2 and alkaline phosphatase (ALP) and decreased VSMCs markers, including smooth muscle (SM) α-actin and SM22-α in a dose-dependent manner. The essential role of FKN/CX3CR1 in VSMCs calcification was further confirmed by lentivirus-mediated knockdown or overexpression of CX3CR1 blocked or accelerated osteogenic transformation of VSMCs. This response was associated with reciprocal up- and down-regulation of osteogenic factor, runt-related transcription factor 2 (RUNX2), transcription factors in osteoclast differentiation, receptor activator of nuclear factor-κB (RANK), RANK ligand (RNAKL) and osteoprotegerin (OPG), respectively. Inhibition of FKN/CX3CR1-activated Jak2/Stat3 signaling by the Jak/Stat inhibitor AG490 blocked osteogenic transformation of VSMCs and RUNX2 induction concurrently. Taken together, our data uncovered novel roles of FKN/CX3CR1 in promoting VSMC osteogenic transformation and atherosclerotic calcification by activating RUNX2 through Jak2/Stat3 signaling pathway and suppressing OPG. Our findings suggest that targeting FKN/CX3CR1 may provide new strategies for the prevention and treatment of atherosclerotic calcification.